Wind power approval, decentralization, and NIMBYism: Evidence from the Swedish Greens - Erik Lundin (Research Institute of Industrial Economics (IFN), 2023)
Green parties are commonly seen as strong proponents of wind power. This paper presents an alternative view, examining data from the highly decentralized institutional setup in Sweden where approval of wind power applications is delegated to local governments. I demonstrate that the approval rate of land based wind power drops by 11 percentage points (from 49 % to 38 %) in municipalities where the Greens are in the ruling coalition, conditional on the share of Green seats in the local council. The association is identified using a twoway fixed-effects logit model with panel data on electoral outcomes from six election terms (2000-2020) in 290 municipalities, combined with detailed data on every application for wind power in Sweden. No statistically significant effect is found for any other of the main parties. A likely mechanism is that even if the Greens have relatively stronger preferences for climate policy than other parties, they are also relatively more concerned about local environmental disamenities caused by wind power. Since decision making is decentralized, local environmental concerns dominate preferences for climate policy, which should be especially pertinent in small municipalities. In line with this argument, I also show that the effect is inversely correlated with municipality population size.
Keywords: D62; D72; H73; P18; Q48; 330; Wind power; decentralization; negative externalities; electricity market; energy transition; climate policy; elections; NIMBYism; Green Party